Bean yield and root development in different soil managements under a center pivot system - de Azevedo, Leonardo Pretto, author; Saad, João Carlos Cury, author; de Aguiar e Silva, Marcelo Augusto, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
The bean culture is part of crop rotation used by irrigators from the southwestern region of the state of São Paulo, who perform the no-tillage soil management as a form of sustainable soil use. The effect of this conservationist practice on soil compaction, root development and bean culture production components in relation to the conventional management was the objective of this work. The experiment was conducted at the Buriti-Mirim Farm, Angatuba, SP, Brazil, using an 18ha area irrigated through center pivot system divided into two types of soil managements: conventional management and no-tillage management. Crop production components, soil cone index and root development components (distribution in the soil profile, length, surface, diameter and dry matter) were evaluated. Although the no-tillage management had presented lower compaction at the most superficial layers and more uniform root distribution in the soil profile, the managements evaluated were not significantly different in relation to crop productivity.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.